Cryobanking crop genetic resources for future generation - Panis, Bart; Popova, Elena (2023)
Cryopreservation is the method of choice to preserve biological material for the long term and effective to transport medical samples over long distances, and store them for prolonged periods of time, but also to create a bank of samples for users. Especially the latter is of great interest for safe conservation of plant genetic resources for future generations. First published results on cryopreservation of plant tissues date back to 60ties but it took until the 90ties before this methodology was applied to store important amounts of crop genetic resources. Cryopreservation is especially useful for those plant species that are not stored through seeds at -20°C and is applied to a wide diversity of totipotent tissues such seeds, embryogenic axes, calli, cell suspension cultures, dormant buds and meristems. Cryopreservation of pollen is also practiced but this often in the framework of breeding programs. Successful cryopreservation relies on avoiding lethal ice crystals formation when exposing the biological tissues to ultra-low temperatures. This can only be reached through vitrification of the cell solutes. To accomplish this, a diversity of cryopreservation protocols was developed often targeting specific tissues; dehydration protocols are especially suitable for pollen and seeds, slow freezing for non-organized tissues such as calli and cell suspensions and (droplet) vitrification for meristematic tissues. While published protocols are described for 100dreds of species, only 7 species have cryopreserved collections of 1000 accessions or more; apple, banana, citrus, mulberry, garlic, berries and potato. In this presentation, state of the art, challenges and prospects of cryopreservation will be discussed.